2016
DOI: 10.21649/akemu.v22i4.1468
|View full text |Cite
|
Sign up to set email alerts
|

Weaning Practices and Perceptions of Mothers Residing in Urban Slums of Lahore, Pakistan: A Focus Group Design

Abstract: Objectives: Current study aimed to explore the perceptions and practices about weaning among mothers of children from 6 months to 2 years of age. Method: An exploratory qualitative research using methodology of focus group discussions (FGD) was conducted on mothers of 6 months to 2 years of age children in urban slums of Lahore. Perceptions and practices of mothers regarding weaning foods were explored through 3 FGDs (n = 30) conducted in the Government dispensaries in 3 conveniently selected slum areas of Lah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, complementary feeding has been recognized to be one of the most often compromised and wrongly practiced in a child’s developmental stage. Early initiation and improper weaning practices are common practices in cultures around the world 9 , 10 . While some mothers give their children other diet apart from breast milk right from birth, others delay additional diet until more than nine months, with either case resulting into over or under-nutrition 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, complementary feeding has been recognized to be one of the most often compromised and wrongly practiced in a child’s developmental stage. Early initiation and improper weaning practices are common practices in cultures around the world 9 , 10 . While some mothers give their children other diet apart from breast milk right from birth, others delay additional diet until more than nine months, with either case resulting into over or under-nutrition 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This poor knowledge might be due to confusing advices received from relatives, and the inconsistency in information among various internet websites. Previous study revealed congruent findings(Al-Shoshan, 2007;Salim et al, 2016). According toFolasade et al (…”
mentioning
confidence: 83%
“…They revealed inconsistency regarding the definition of weaning; for instance, the dominant definition of weaning was to completely stop breastfeeding and start introducing soft foods while some participants believed in continuation of breastfeeding along with introducing soft foods.This inconsistency in the definition of weaning might be attributed to poor knowledge among Jordanian mothers, insufficient health education received by health professionals and sharing childcare issues with the extended family members and friends who have different views about weaning. Mother's knowledge about weaning is a very crucial factor to decrease malnutrition and feeding problems(Salim, Kalsoom, & Humayun, 2016), and consequently, decrease the morbidity and mortality rates among children. Similarly, a study conducted byAnderson et al (2001) found that there was inconsistency in the definition of weaning between healthcare providers and mothers in Fife/Scotland.…”
mentioning
confidence: 99%
“…Tea, crackers, and rusk are often used during the weaning period in disadvantaged households because they are inexpensive and readily available. (13) . Most important purpose of this research was to find out the infant mothers' knowledge of the value of weaning correlated with their educational level, work, and maternal physical and financial health of families.…”
Section: Introductionmentioning
confidence: 99%